Sandblasting & pintura industrial power cleaning (2009)
Based on the business idea of ​​four friends who are now back, with the desire to add knowledge and experiences, the initiative emerged to study the feasibility of a company that provides Sandblasting and Industrial Painting in the department of Quindío.